2011
DOI: 10.3201/eid1701.100886
|View full text |Cite
|
Sign up to set email alerts
|

Serotype Distribution and Drug Resistance inStreptococcus pneumoniae, Palestinian Territories

Abstract: To determine antimicrobial drug resistance of Streptococcus pneumoniae serotypes, we analyzed isolates from blood cultures of sick children residing in the West Bank before initiation of pneumococcal vaccination. Of 120 serotypes isolated, 50.8%, 73.3%, and 80.8% of the bacteremia cases could have been prevented by pneumococcal conjugate vaccines. Serotype 14 was the most drug-resistant serotype isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Congruently, results obtained from a carriage study on healthy Israeli children aged below 36 months showed the added benefit of an extended serotype coverage by the PCV13 vaccine over the PCV7 vaccine of 21%, raising it from 46% to 67% [40]. Employing the PCV13 vaccine increases the cross-protective spectrum, at least against strains of the serotypes 6A, 19A, 3 and 1, which were also mentioned by Kattan et al, and are also responsible for IPD among Palestinian children [20]. The results from testing antimicrobial susceptibility of the strains of S. pneumoniae isolated from the Palestinian children in relation to the strain's serotypes, as mentioned above and discussed below, also support recommending using the PCV13 vaccine in the NIP in the West Bank.…”
Section: Discussionmentioning
confidence: 86%
“…Congruently, results obtained from a carriage study on healthy Israeli children aged below 36 months showed the added benefit of an extended serotype coverage by the PCV13 vaccine over the PCV7 vaccine of 21%, raising it from 46% to 67% [40]. Employing the PCV13 vaccine increases the cross-protective spectrum, at least against strains of the serotypes 6A, 19A, 3 and 1, which were also mentioned by Kattan et al, and are also responsible for IPD among Palestinian children [20]. The results from testing antimicrobial susceptibility of the strains of S. pneumoniae isolated from the Palestinian children in relation to the strain's serotypes, as mentioned above and discussed below, also support recommending using the PCV13 vaccine in the NIP in the West Bank.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, susceptibility to erythromycin and cotrimoxazole were lower at 68.3% and 38.3% respectively and serotype 14 was indeed responsible for majority (75%) of the less susceptible isolates from these two classes of antibiotics. This is further supported by the fact that 53.3% of serotype 14 isolates were resistant to two or more antibiotics [133].…”
Section: Palestinementioning
confidence: 83%
“…PCV7 coverage is estimated to be 55.0% (including serogroup 18) while PCV10 and PCV13 cover 77.5% and 85.0% of the isolates, respectively. The prevalence was predicted based on patients <11 years old suspected with sepsis or endocarditis, but no meningitis or pneumonia cases were included due to the rare occurrence of these infections in Palestine [133]. Overall, all were susceptible to vancomycin and almost all (98.3%) of the isolates were susceptible to penicillin and ofloxacin [133].…”
Section: Palestinementioning
confidence: 99%
See 1 more Smart Citation
“… 3 The management of streptococcal-related pneumonia is made more difficult by the appearance of several antimicrobial or resistant germs. 4 , 5 Therefore, the successful treatment of drug-resistant pneumococcal pneumonia represents a challenge for physicians. There is an association between the usage of antiseptic agents and the occurrence of resistance in S. pneumoniae .…”
Section: Introductionmentioning
confidence: 99%